Online Analysis of Handwriting for Disease Diagnosis: A Review - Kedar, Seema; S. Bormane, D.; Joshi, Sandeep (International Journal of Engineering and Technology, 2018)
Background/Objectives: Handwriting is an action governed by brain like any other action. This process is usually unconscious and is closely tied to impulses from brain. Any kind of disease affects the kinetic movement and reflects in subjectâ€™s handwriting. To understand the health and mental problems, it is important to focus on how subject writes instead of what subject writes. This also makes the process of handwriting analysis independent of any language. Handwriting analysis is a pseudo-science used to study physical and behavioral characteristics of handwriting. In this paper, the general approach used for the disease diagnosis based on digital handwriting analysis has been presented. The research work carried out to diagnose diseases such as Alzheimer, Mild Cognitive Impairment, Dysgraphia, Schizophrenia, Autism, Parkinsonâ€™s disease and Mental illness based on digital handwriting analysis has been reviewed in this paper. The features related to motion, time and pressure have been used for diagnosis of disease. The experiments and results are also summarized in this paper.Â